SUBSTANTIATION OF PARAMETERS OF THE PLAN TO ELIMINATE THE BARRIER LINES INCLUDE THE RENOVATION OF THE RAILWAY - Rybkin, V. V.; Kurhan, M. B.; Khalipova, N. V.; Kharlan, V. I. (Science and Transport Progress, 2003)
An approach has been proposed to substantiation of the track plane parameters with the aim of removal of barrier places. The approach is based on modelling spatial fluctuations of freight and passenger cars and provides for comfort of passenger journeys at introduction of high-speed traffic.